Efficacy of polyvinylpyrrolidone-capped gold nanorods against 7, 12 dimethylbenz(a)anthracene-induced oviduct and endometrial cancers in albino rats. Issue 1 (31st December 2023) - Gamal, Hend; Tawfik, Walid; El-Sayyad, Hassan H; Fahmy, Heba Mohamed; Emam, Ahmed N.; El-Ghaweet, Heba A
ABSTRACT: Polyvinylpyrrolidone-capped gold nanorods (PVP-capped AuNRs) are emerging as promising agents for cancer therapy. With the widespread utilization of nanoparticles, some is known about the therapeutic effect of PVP-capped AuNRs on oviduct and endometrium adenocarcinomas resulting from 7, 12-dimethylbenz[a]anthracene (DMBA)-induced carcinogenesis. Twenty-four female Wister albino rats ( Rattus norvegicus ) were categorized into four groups: negative control, PVP-capped AuNRs positive control, DMBA-treatment and DMBA plus PVP-capped AuNRs. A fabrication method of PVP-capped AuNRs and their characterization was assessed using ultraviolet spectra (UV), ultrastructure analysis, dynamic light scattering (DLS) and zeta potential (ɳ). Morphometric assessments and the mortality rate after induction with DMBA carcinogenesis were recorded. The oviducts and uteri were dissected and subjected to histopathological and immunohistochemical analysis. PVP-capped AuNRs treatment enhanced the histological features of the DMBA carcinogenesis-dependent oviduct and endometrium adenocarcinomas. In addition, there was a reduced immune reaction of caspase-3 and Ki-67 markers after the treatment, with PVP-capped AuNRs referring to its improvement effect. In conclusion, PVP-capped AuNRs showed therapeutic potential against oviduct and endometrium adenocarcinoma by reaching tumors via enhancing permeability and retention effect. The proposed methodology suggests that PVP-capped AuNRs target the site and the boundaries of cancer, opening new therapeutic options.